The Value of 1H-MRS and MRI in Combined Methylmalonic Aciduria and Homocystinuria. Issue 4 (July 2019) - Cheng, Ailan; Yao, Rong; Cao, Wenjun; Yu, Hong
Abstract : Objective: The aims of this study were to describe the brain magnetic resonance imaging (MRI) features of methylmalonic aciduria and homocystinuria and to evaluate the additional value of 1 H-MRS. Patients and Methods: Twenty-eight children with methylmalonic aciduria and homocystinuria were included in this study. The control group included 21 healthy children. All the cases underwent MRI and 1 H-MRS before treatment. We measured the N -acetylaspartate (NAA), choline (Cho), creatine (Cr), and myoinositol (mI) peaks in the basal ganglia regions. The NAA/Cr, Cho/Cr, mI/Cr, and NAA/Cho ratios were calculated. We also observed whether there were lactic acid peaks. Result: We identified that NAA/Cr and NAA/Cho significantly decreased in the basal ganglia and that 3 patients showed lactate peaks, but other metabolites were not significantly altered. Hydrocephalus and diffuse supratentorial white matter edema were the primary MR findings; 7 patients had thinning of the corpus callosum, and 2 patients had subdural hematoma. Six patients showed normal brain MRI findings. Conclusions: Methylmalonic aciduria and homocystinuria patients with metabolite changes in the basal ganglia demonstrate compromised neuronal integrity, and anerobic metabolism occurs in acute encephalopathic episodes. 1 H-MRS is a useful tool for evaluating brain damage. Hydrocephalus and diffuse supratentorial white matter edema are the main MRI features.